Step-by-step process to mainstream gender in climate-smart agricultural initiatives in Guatemala - Acosta, Mariola; Bonilla Findji, Osana; Howland, Fanny C.; Twyman, Jennifer; Gumucio, Tatiana; Martínez Barón, Deissy; Le Coq, Jean-François (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Within the framework of the projects “Generating evidence on gender-sensitive climate-smart agriculture to inform policy in Central America” and “Shaping equitable climate change policies for resilient food systems across Central America and the Caribbean”, during 2018 and 2019, a series of workshops was held at the national level with the purpose of strengthening the capacities of stakeholders to develop and implement agricultural projects integrating gender and climate change perspectives. The need to strengthen the inclusion of gender equality considerations in all phases of agricultural program and project design and implementation was emphasized during these activities, including the need to create more robust monitoring systems integrating gender indicator and measures focused on enhancing the adaptive capacity to cope with the impacts of climate change and variability. Within this context MAGA and CCAFS joined efforts to prepare this guide as a practical tool to orient stakeholders at the national or sub-national level in designing, implementing, and monitoring interventions seeking to promote a climate-smart agriculture (CSA) so that they consider and reflect a gender equality approach.